Exploring the Health Care Challenges and Health Care Needs of Arabic-Speaking Immigrants with Cardiovascular Disease in Australia - Erini Abdelmessih; Maree-Donna Simpson; Jennifer Cox; Yann Guisard (MDPI AG, 2019)
The Arabic-speaking immigrant group, which makes up the fourth largest language group in Australia, has a high prevalence of cardiovascular disease. The objective of this study was to explore the health care challenges and needs of Arabic-speaking immigrants with cardiovascular disease (CVD), using a comparative approach with English-speaking patients with CVD as the comparable group. Methods: Participants were recruited from community settings in Melbourne, Australia. Face-to-face semi-structured individual interviews were conducted at the recruitment sites. All interviews were audio-taped, transcribed, and coded thematically. Results: 29 participants with CVD were recruited; 15 Arabic-speaking and 14 English-speaking. Arabic-speaking immigrants, and to a lesser extent English-speaking patients with CVD may have specific health care challenges and needs. Arabic-speaking immigrants’ health care needs include: effective health care provider (HCP)-patient communication, accessible care, participation in decision-making, and empowerment. English-speaking participants viewed these needs as important for CVD management. However, only a few English-speaking participants cited these needs as unmet health care needs. Conclusion: This study suggests that Arabic-speaking immigrants with CVD may have unique needs including the need for privacy, effective HCP-patient communication that takes into account patients’ limited English proficiency, and pharmacist-physician collaboration. Therefore, there may be a need to identify a health care model that can address these patients’ health care challenges and needs. This, in turn, may improve their disease management and health outcomes.